Sensitivity and Susceptibility of the Yahara River to Petroleum Spills - Sommers, Robert; Lloyd, Traci; Grisbeck, Derek (My University, 2011)
Identify and map the riparian, wetland and lake shore areas of the Yahara River in Dane County, Wisconsin that are most sensitive and susceptible to petroleum spills. This information could be used to more efficiently coordinate protection and cleanup efforts.
Includes Tables, Figures, Maps, Appendices and Bibliography.
Keywords: Petroleum Spills; Yahara River